Applying rice seed-associated antagonistic bacteria to manage rice sheath blight in developing countries - Mew, T.W.; Cottyn, Bart; Pamplona, Raymond; Barrios, Helen; Xiangmin, Li; Chen, Zhiyi; Fan, Lu; Nil-panit, Nongrat; Arunyanart, Parkpian; Van Kim, Pham; Van Du, Pham (Scientific Societies, 2004)
One promising area of disease management for resource-poor farmers that emerged in recent years in developing countries is the potential of biological control. Biological control agents (BCAs) were found to be ubiquitous in the rice ecosystem. Seed bacterization with BCAs appeared to promote plant growth. BCAs showed efficacy on sheath blight (Rhizoctonia solani AG 1) but produced inconsistent results over time in the field using it alone. The control efficiency ranged from 50 to over 90%, with a high variance. To improve the efficacy, a half-dose of a commonly used fungicide, like Jingangmycin in China and Validamycin in Vietnam, was introduced to mix with BCAs and was found to be effective, and it reduced the variance of the field performance tests. To scale up the BCA technology for resource-poor farmers, a participatory approach, engaging the farmers to evaluate the product, was initiated in China and Vietnam. The BCA strain that is indigenous at a locality is mass produced at the research institution based on the total area required for application, as relayed by the farmers to extension workers. The demand by farmers would serve as the basis for the amount to be produced and for delivery to the rice farmers who were participating in the trials and, later, to those farmers who ordered the product. This process alleviates BCA storage and shelf-life problems. Data from the field performance trials also were used by the researchers to apply for registration for commercial use of BCAs. Scaling up to extend the BCA technology to more rice farmers as an integral part of their pest management scheme, in particular, and crop management practices, in general, is foreseen in the near future.